Aesthetic Aspects of the novel "Decline of Colonel" - Khodabakhsh Asadollahi; Leila Azarnivar (مطالعات زبانی و بلاغی)
Aesthetic truth is an event that instantly evokes the concept of instability and vibrational motion of truth. Based on his understanding of beauty and art, the author finds a relationship with his imaginative power that makes the truth and essence of art and beauty the source of his work of art. In fact, recognizing the aesthetic qualities resulting from the search for sufficient beauty conditions, shows with what qualities the work evokes beautiful and sublime feelings in us. In the present study, the aesthetic aspects of "Decline of Colonel" by Mahmoud Dolatabadi have been studied using a descriptive-analytical method. While introducing and presenting the summary of the story, the most used aesthetic elements include simile, metaphor, irony, imagination, recognition, symbol, allusion, etc. As a result, the author had a wide choice for emplying poetic elements in the novel, and he has used imaginary forms, especially similes, to express similar situations and express the inner feelings of the characters, and has created an atmosphere that can make a deep impact on the audience.